Preventive preservation efforts in museum libraries - Ilyasa, Diaz (Record and Library Journal, 2023)
Background of the study: The Asian-African Conference Museum Library collection in this library is a historical witness for present and future generations regarding the Asian-African Conference, which required preventive and curative preservation measures so that the collection could continue to be accessed. Purpose: This research aims to explain how the preventive preservation activities of library collections in the Asia-Africa conference museum library and can be used as a reference for other libraries in their collection preservation activities. Method: This qualitative research uses a descriptive method. The sample were conducted by purposive sampling method. Data collection techniques used in this study were observation, interviews, and literature review. In this research, source triangulation was used in testing the validity of the research data. Findings: The Asian-African Conference Museum Library has implemented several measures to preserve library collections. There are preventive preservation efforts such as routine room cleaning, dust cleaning using a vacuum cleaner, fumigation measures, appeals for users to take off their footwear before entering the library, to assisting users who will access the collection room. Conclusion: The Asian-African Conference Museum Library has made various efforts to preserve library collections so that they remain durable and can always be accessed by users